Modern attempts at drug treatment of fetal growth retardation in different terms of pregnancy - Deinichenko, O. V.; Krut`, Yu. Ya.; Дейніченко, Олена Валеріївна; Круть, Юрій Якович (My University, 2019)
Diagnosis, treatment, and prevention of fetal growth retardation (FGR) is one of the urgent problems of modern obstetrics [1–6]. According to various authors [4,5], the prevalence of this syndrome in various obstetric pathologies ranges from 11% to 36%. In recent years, the incidence of FGR syndrome has been increasing. This is due to both the improvement of antenatal diagnosis and the instability of socio-economic conditions in modern society.
Keywords: тези доповідей